A Mathematical Model for Solving Distribution System Problem by Considering Odd-Even Vehicle License Plate Rule - Nugraha, Andika Dwi; Winarno, Winarno; Hadining, Aulia Fashanah (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2021)
This research discusses the goods distribution system in an urban area by considering an odd-even vehicle license plate rule. This rule enables the vehicles with the even-number plate to pass particular roads on even-number dates and vice versa during specific time intervals determined by the authority. This rule is potentially rising the company’s logistic cost up to 20%. Therefore, a Mixed-Integer Linear Programming model is developed to solve the problem. The performance of the model is tested on some numerical examples. Computational results show that the model generates optimal solutions with numerous computational times. The instances of customers located randomly and clustered manner (i.e., mix) are arduous to solve. The average computational time of these instances is 1 hour and 35 minutes.